2013
DOI: 10.3727/096368913x672109
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Granulocyte Colony-Stimulating Factor (G-CSF) Administration for Postrehabilitated Motor Complete Spinal Cord Injury Patients: An Open-Label, Phase I Study

Abstract: Granulocyte colony-stimulating factor (G-CSF) is a major growth factor in the activation and differentiation of granulocytes. This cytokine has been widely and safely employed in different conditions over many years. In this translational study, G-CSF is administered to 19 patients with chronic motor complete spinal cord injury, and outcomes are reported. All 19 patients received subcutaneous G-CSF (5 µg/kg per day) for 5 days and were followed for at least 6 months. The American Spinal Injury Association (ASI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…With the same rationale, we chose incomplete (AIS grade B-D) TSCIs for this study and considered subcutaneous G-CSF as a safe intervention. 6 According to our results, the greatest change in AIS grade in the G-CSF group was observed among AIS grade B and C patients. However, improvement in AIS grade D was less common than in AIS grade B or C patients.…”
Section: Prognosticationsupporting
confidence: 49%
See 2 more Smart Citations
“…With the same rationale, we chose incomplete (AIS grade B-D) TSCIs for this study and considered subcutaneous G-CSF as a safe intervention. 6 According to our results, the greatest change in AIS grade in the G-CSF group was observed among AIS grade B and C patients. However, improvement in AIS grade D was less common than in AIS grade B or C patients.…”
Section: Prognosticationsupporting
confidence: 49%
“…38 Secondary injury may be an appropriate target for neuroprotective and clinical therapeutic interventions, 12,37 such as methylprednisolone sodium succinate (MPSS) and the related compound tirilazad mesylate, 4,9 nimodipine, 24 naloxone, 10 gancyclidine (N-methyl-d-aspartate antagonist), 32 and granulocyte colony-stimulating factor (G-CSF). 6,14,27,33 G-CSF has already been reported to have positive effects on the course of various neurological disorders experimentally, such as stroke, 30 Parkinson's disease, 20 Alzheimer's disease, 34 amyotrophic lateral sclerosis, 23 sciatic nerve injury, 17 partial cochlear nerve lesion, 21 traumatic brain injury, 31 and various rodent models of TSCI. 22 Multiple preclinical studies in TSCI models have suggested several mechanisms for the neurorestorative effects of G-CSF, including antiapoptotic activity, stem cell mobilization, angiogenesis, neurogenesis, and immunomodulation through specific signaling pathways.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The higher grades of injuries were correlated with poorer results. The article only assessed the chronic phase of injury and did not compare it with other treatment modalities (24). In a retrospective study conducted by Kamiya and colleagues in 2015, two groups of nonrandomized partial SCI treated by G-CSF and high-dose methylprednisolone followed up to three months were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Derakhshanrad et al recruited 19 patients, all of whom received G‐CSF (5 µg kg −1 day −1 ) subcutaneously for 5 days 235. Some patients showed mild side effects (rash, fever, bone pain, neuropathic pain, and spasticity) that disappeared in a week.…”
Section: Clinical Studiesmentioning
confidence: 99%